Entre cartas e jornais : os discursos sobre a Guerra do Paraguai (1864-1870) como uma afirmação identitária - Cerqueira, Monique Hellen Santos Reis (2019)
The War of the Paraguay (1864-1870) or War of the Triple Alliance commonly called more by the platinum countries was one of the events of the Second Empire responsible for promoting an incipient feeling of belonging among the Brazilians of century XIX. In this way, the research sought to understand the political strategies used by the Empire with the war, analyzing the political identity that was forged during the same, so that it maintained the concordance and stability between the provinces, besides all symbolic representativeness to manipulate this construction in the imaginary postwar society. It is pertinent to the ideology created about war and reflected in the question of identity as a tool used to integrate and consecrate the monarchy. Thus, primary sources were used as the main newspapers in circulation of the time, since the periodicals were networks of sociability that allowed to express the ideological debates of a certain social group and its power of influence in the masses; two letters of the Baron of Mauá (1813-1889) sent to Manuel Antônio da Rocha Faria (1830-1894), one of the leaders of the body of Volunteers of Bahia and the adviser José Maria Paranhos (1819-1880) referring to the tensions and negotiations before and post-conflict, two letters from Francisco Octaviano de Almeida Rosa (1825-1889) to the Baron of Penedo (1815-1916) discussing the political situation of the Empire, as well as a document on the construction of a gunpowder factory in the province of Mato Grosso removing the "innocence" of a Brazil that did not think about a war. In addition, we perceive that the party political game influenced to the weakening of the political strategies around the war despite the symbolic construction evoked on the patriotism by the intellectuals in the newspapers.